Factors Associated with Coping Behaviors of People Affected by the Unrest in the Deep South of Thailand - ยาโกะ กษมา; จำปากลาย อารี (Princess of Naradhiwas University Journal, 2018)
The violence situation in southernmost provinces of Thailand inevitably affects the quality of life of people living in those areas. The objectives of this research were to explore the behaviors of problemfocused coping and to analyze the relations between demographic factors, violence experience, social support, and coping behaviors of people affected by the unrest in the southernmost provinces of Thailand. The data were collected using face-to-face interviews with 422 Thai Muslims aged 15-59 years old who live in Nong Chik District of Pattani Province. Probability Proportional to Size (PPS) sampling was used. The statistical methods include frequency, percentage, mean, standard deviation, and Chi-squared test. The results show that the samples use a method of problem-focused coping at a moderate level ( =3.03, S.D. =0.80). The statistically significant factors related to problem-focused coping behaviors were sex (χ2=7.395, p<0.05), secular education (χ2 =12.814, p<0.05), religious education (χ2 =26.355, p<0.001), violence experience (χ2 =31.995, p<0.001), social support from family (χ2 =78.109, p<0.001), friends (χ2 =43.657, p<0.001) and social institutions (χ2 =31.075, p<0.001). The study indicated the need to develop and apply a policy that would promote social support from family, friends, and social institutions to people who affected by the unrest situation to coping with the problems effectively.